OCORRÊNCIA DE PSEUDOMONAS CICHORII EM TOMATEIRO NO ESTADO DE SÃO PAULO - Silva, T.a.f. [UNESP]; Beriam, L.o.s. [UNESP]; Azevedo, S.m.; Gioria, R.; Almeida, I.m.g.; Maringoni, A.c. [UNESP] (Instituto Biológico, 2021)
Recently, generalized blight symptoms were observed in tomato leaves of the types Salad and Italian, at two commercial fields located in Bragança Paulista and Mogi Guaçú, SP, Brazil. The presence of bacterial exudation was verified in observations of infected tissues under an optical microscope. Isolation attempts allowed the recovery of rod-shaped, Gram-negative bacteria, in white colonies that produced fluorescent pigment in King’s B medium. Bacterial isolates were submitted to LOPAT tests and classified into group III (+ +); consequently, they were identified as Pseudomonas cichorii. These results were corroborated by indirect immunofluorescence tests, using antisera produced for the type strain of P. cichorii. This bacterium causes diseases in several crops of economic importance, and had not yet been observed on tomatoes in Brazil. Bacterial isolates have been deposited with the Phytobacteria Culture Collection of the Instituto Biológico, under accession numbers IBSBF 2309 and IBSBF 2323.

Recentemente, em dois campos comerciais de tomateiro dos tipos Salada e Italiano, localizados em Bragança Paulista e Mogi Guaçú, SP, foram observados sintomas de queima generalizada nas folhas. Em observações, ao microscópio óptico, de tecidos infectados, foi constatada a presença de exsudação bacteriana. Desses tecidos, foram isoladas bactérias em formato bastonete, Gramnegativas, com colônias de coloração branca e produtoras de pigmento fluorescente em meio B de King. Isolados bacterianos foram submetidos aos testes LOPAT, sendo enquadrados no grupo III (+ +) e, portanto, identificados como sendo Pseudomonas cichorii. Esses resultados foram corroborados por testes serológicos de imunofluorescência indireta, com antissoros produzidos para linhagem tipo de P. cichorii. Esta bactéria causa doença em várias culturas de importância econômica e ainda não havia sido constatada no Brasil na cultura de tomateiro. Os isolados bacterianos foram depositados na Coleção de Culturas de Fitobactérias do Instituto Biológico, sob os números de acesso IBSBF 2309 e IBSBF 2323.
OCCURRENCE OF PSEUDOMONAS CICHORII ON TOMATOES IN SÃO PAULO STATE, BRAZIL
Keywords: Lycopersicon esculentum; leaf blight; LOPAT tests; Lycopersicon esculentum; queima de folhas; testes LOPAT